1999
DOI: 10.1016/s0005-2736(99)00083-8
|View full text |Cite
|
Sign up to set email alerts
|

Elicitins trap and transfer sterols from micelles, liposomes and plant plasma membranes

Abstract: Using elicitins, proteins secreted by some phytopathogenic Oomycetes (Phytophthora) known to be able to transfer sterols between phospholipid vesicles, the transfer of sterols between micelles, liposomes and biological membranes was studied. Firstly, a simple fluorometric method to screen the sterol-carrier capacity of proteins, avoiding the preparation of sterol-containing phospholipidic vesicles, is proposed. The transfer of sterols between DHE micelles (donor) and stigmasterol or cholesterol micelles (accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 26 publications
2
48
0
1
Order By: Relevance
“…The purified proteins (native state) from both Phytophthora and Pichia culture filtrates are "void," i.e., sterol-unloaded proteins, as it appeared in this work and from structural (Boissy et al, 1996;Fefeu et al, 1997;Gooley et al, 1998) and chemical (Mikes et al, 1997(Mikes et al, , 1998 analyses. It was previously reported that elicitins easily bind sterols from tobacco plasma membranes (Vauthrin et al, 1999). Thus, during ligand replacement and binding experiments elicitins can load sterols.…”
Section: Role Of Sterol-elicitin Complexes In Elicitin Binding To Spementioning
confidence: 96%
See 3 more Smart Citations
“…The purified proteins (native state) from both Phytophthora and Pichia culture filtrates are "void," i.e., sterol-unloaded proteins, as it appeared in this work and from structural (Boissy et al, 1996;Fefeu et al, 1997;Gooley et al, 1998) and chemical (Mikes et al, 1997(Mikes et al, , 1998 analyses. It was previously reported that elicitins easily bind sterols from tobacco plasma membranes (Vauthrin et al, 1999). Thus, during ligand replacement and binding experiments elicitins can load sterols.…”
Section: Role Of Sterol-elicitin Complexes In Elicitin Binding To Spementioning
confidence: 96%
“…The iodination of elicitin changed neither the previously described effects of the elicitor on tobacco cells nor the sterol carrier activity (Osman, Vauthrin, Mikes, Milat, Panabières, Marais, Brunie, Maume, Ponchet, and Blein, unpublished results). Plasma membrane-enriched fractions were obtained as previously reported (Vauthrin et al, 1999). Binding experiments and ligand replacement experiments were carried out as already reported .…”
Section: Binding and Ligand Replacement Experiments With The Use Of 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, elicitins catalyze sterol transfer between phospholipidic artificial membranes [49,50]. They are also able to trap sterols from biological membranes (plant cell suspensions or purified plasma membranes) and to transfer sterols from liposomes to isolated plasmalemma vesicles [51]. In addition, elicitins bind fatty acids and phospholipids.…”
mentioning
confidence: 99%